2003
DOI: 10.1038/sj.bjc.6601336
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo analysis of topotecan: advancing the application of laboratory-based clinical therapeutics

Abstract: Topotecan is currently approved for relapsed small-cell lung cancer and ovarian cancer. Topotecan's efficacy in the second-line setting and novel mechanism of action suggest broad antitumour activity. We utilised a clinically validated, cell-death, ex vivo assay in human tumour explants to examine the activity profile of topotecan alone and in combination with other antitumour agents. Serial dilutions of topotecan alone and in combination with other cytotoxic agents were applied to biopsy specimens of non-smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In a patient population with a poor prognosis and potential comorbidities, there is a clear need for noncross-resistant therapeutic options. It's reversible, nonoverlapping nonhematologic toxicities and in vitro antitumor synergy with platinum agents, taxanes, and topoisomerase II inhibitors may make topotecan an ideal candidate for use in combination with other chemotherapy agents [44][45][46].…”
Section: Topotecan-based Combinationsmentioning
confidence: 99%
“…In a patient population with a poor prognosis and potential comorbidities, there is a clear need for noncross-resistant therapeutic options. It's reversible, nonoverlapping nonhematologic toxicities and in vitro antitumor synergy with platinum agents, taxanes, and topoisomerase II inhibitors may make topotecan an ideal candidate for use in combination with other chemotherapy agents [44][45][46].…”
Section: Topotecan-based Combinationsmentioning
confidence: 99%
“…During DNA replication and repair, the enzyme topoisomerase 1 creates single strand breaks in the DNA. Camptothecin forms a tertiary complex with topoisomerase 1 and the cleaved DNA, thereby blocking the annealing of DNA sister strands [4, 30]. This camptothecin-DNA-Topoisomerase 1 complex causes DNA damage and eventually leads to cellular apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-oriented studies show that camptothecin is active against brain metastases in SCLC [4, 30]. The clinic profile of camptothecin, its broad-spectrum anti-tumor activity, and its lack of cross resistance with other anti-cancer agents has prompted clinical studies investigating the feasibility of camptothecin being used in a first-line setting for SCLC patients [4, 5, 31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cells committed to death will overcome exposure to potent caspase inhibitors to die via pathways that mimic necrosis [7••]. Fresh explants of human tumors in culture have provided significant insights, including the first observation of activity for chlorodeoxyadenosine in hairy cell leukemia, synergy between purines and mustard alkylators in lymphoid malignancies [8], the activity and synergy for platins plus gemcitabine in breast and ovarian cancers [9,10], characterization of topotecan combinations [11], and the accurate selection of disease targets for gefitinib [12,13], all of which have been subsequently confirmed in clinical trials. By measuring cell death in primary culture spheroids, the cumulative effect of all of the operative survival and death cascades can be gauged at once.…”
Section: Biological Principlesmentioning
confidence: 99%